Treatment of COVID-19 Pneumonia and Acute Respiratory Distress With Ramatroban, a Thromboxane A2 and Prostaglandin D2 Receptor Antagonist: A Four-Patient Case Series Report - Ogletree, Martin L.; Chander Chiang, Kate; Kulshrestha, Rashmi; Agarwal, Aditya; Agarwal, Ashutosh; Gupta, Ajay (Frontiers in Pharmacology, 2022)
Hypoxemia in COVID-19 pneumonia is associated with hospitalization, mechanical ventilation and mortality. COVID-19 patients exhibit marked increases in fatty acid levels and inflammatory lipid mediators, predominantly arachidonic acid metabolites, notably thromboxane B2 >> prostaglandin E2 > prostaglandin D2. Thromboxane A2 increases pulmonary capillary pressure and microvascular permeability, leading to pulmonary edema, and causes bronchoconstriction contributing to ventilation/perfusion mismatch. Prostaglandin D2-stimulated IL-13 production is associated with respiratory failure, possibly due to hyaluronan accumulation in the lungs. Ramatroban, is an orally bioavailable, dual thromboxane A2/TP and prostaglandin D2/DP2 receptor antagonist used in Japan for allergic rhinitis. Four consecutive outpatients with COVID-19 pneumonia treated with ramatroban exhibited rapid relief of dyspnea and hypoxemia within 12-36 hours and complete resolution over 5 days, thereby avoiding hospitalization. Therefore, ramatroban, as an anti-vasospastic, broncho-relaxant, anti-thrombotic and immunomodulatory agent merits study in randomized clinical trials that might offer hope for a cost-effective pandemic treatment.